2015
DOI: 10.4047/jap.2015.7.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between squamous cell carcinoma of the tongue and the position of dental prosthesis

Abstract: PURPOSESquamous cell carcinoma (SCC) of the tongue has a relatively high incidence of all oral cancers. Some studies have reported a relationship between intraoral dental prosthesis and SCC of the tongue; however, this relationship remains controversial. The purpose of this study was to investigate the relationship between SCC of the tongue and the positional aspects of dental prosthesis using a retrospective analysis.MATERIALS AND METHODSA total of 439 patients with SCC of the tongue were diagnosed and treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Because OSCC occur predominantly at sites of denture trauma, the scientific community has been asking whether chronic dental trauma and irritation are carcinogenic . We investigated the association of dental trauma with LOH, an early genetic change in oral tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because OSCC occur predominantly at sites of denture trauma, the scientific community has been asking whether chronic dental trauma and irritation are carcinogenic . We investigated the association of dental trauma with LOH, an early genetic change in oral tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco and alcohol use are the classical etiologic factors for oral squamous cell carcinoma (OSCC). Chronic trauma is suggested to be an additional etiologic risk factor for OSCC, and patients with crowns and/or bridges exhibited higher frequency of OSCC in the tongue compared to patients without these prostheses . Moreover, OSCC occurs predominantly at sites of potential dental and denture trauma, especially in non‐smoker patients .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in animal models have shown that there is an effect of ethanol on the penetration of nitrosonornicotine (From tobacco) into the oral mucosa. [33] CONCLUSION This clinical retrospective study included 48 patients having chronic non-healing ulcer(s) in the oral cavity between the interval of July 2014 and March 2016. On histopathological examination, 42 patients were found to be OSCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 Few articles have also indicated the effects of sharp tooth, edentulousness and para-functional habits in causing deleterious effects on the oral mucosa. 8,9,11 The irritation of oral mucosa during orthodontic treatment needs attention in this regard. Worldwide, tobacco use is a leading cause of deaths amounting to above five million per year, and based on the current scenario it can be assumed that tobacco usage would cause around ten million cases of mortality annually by the year 2030.…”
Section: Introductionmentioning
confidence: 99%